Comparison of the SPF Values of 70% and 96% Ethanol Extracts of Bandotan Leaves (Ageratum conyzoides L.) Using the UV-Vis Spectrophotometric Method - Dewianisya Arifatussholiha; Annie Rahmatillah; Rahmat Hidayat (Jurnal FARMASIMED (JFM), 2026)
Indonesia, as a tropical country, has high exposure to ultraviolet radiation that can cause skin damage. Bandotan leaves (Ageratum conyzoides L.) contain flavonoids and tannins capable of absorbing UV radiation, thus having potential to be developed as a safer natural sunscreen agent. This study aimed to determine the Sun Protection Factor (SPF) values of 70% and 96% ethanol extracts of bandotan leaves using the UV-Vis spectrophotometric method and to evaluate the effect of different ethanol solvent concentrations on the SPF values of the extracts. The study used dried bandotan leaf simplicia extracted by maceration method with 70% and 96% ethanol. The obtained extracts were subjected to standardization and phytochemical screening. SPF values were determined in vitro using a UV-Vis spectrophotometer at a wavelength range of 290–320 nm with extract concentrations of 20, 40, 60, 80, and 100 ppm, and calculated using the Mansur method. The results showed that the SPF values of the 70% ethanol extract were 1.1550, 1.8349, 2.4004, 3.3868, and 4.5036, respectively, while the 96% ethanol extract produced SPF values of 1.0821, 2.0559, 2.9325, 3.8779, and 5.1098, categorized from no protection to moderate protection. The difference in ethanol solvent concentration (70% and 96%) had a significant effect on the SPF values of bandotan leaf extract (p < 0.05). Based on these findings, it can be concluded that the 96% ethanol extract of bandotan leaves (Ageratum conyzoides L.) is more effective than the 70% ethanol extract in producing photoprotective activity and therefore has potential to be developed as a natural ingredient in sunscreen formulations.